2011
DOI: 10.1093/cvr/cvr345
|View full text |Cite
|
Sign up to set email alerts
|

Gap junctional communication controls the overall endothelial calcium response to vasoactive agonists

Abstract: The global Ca(2+)(i) response of the endothelium to agonists is determined decisively by the functionality of GJs, thus establishing a new role for GJs in controlling endothelial activity and vasomotor function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
35
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 35 publications
6
35
0
Order By: Relevance
“…The SMC tone is further controlled by Ca 2+ signaling in ECs, which is also modulated by both Cx40 and Cx37. 15,16 The physiological relevance of these observations is supported by the findings that the renin-dependent hypertension increases the expression of Cx40 in ECs, as well as that of Cx37 and Cx43 in SMCs, via an angiotensin II-dependent mechanism. 13 To assess the relative importance of Cx signaling on renin secretion and vasomotor function, a previous study has investigated the deletion of Cx40 in either RSCs or ECs, using the Cre-lox technology.…”
mentioning
confidence: 82%
“…The SMC tone is further controlled by Ca 2+ signaling in ECs, which is also modulated by both Cx40 and Cx37. 15,16 The physiological relevance of these observations is supported by the findings that the renin-dependent hypertension increases the expression of Cx40 in ECs, as well as that of Cx37 and Cx43 in SMCs, via an angiotensin II-dependent mechanism. 13 To assess the relative importance of Cx signaling on renin secretion and vasomotor function, a previous study has investigated the deletion of Cx40 in either RSCs or ECs, using the Cre-lox technology.…”
mentioning
confidence: 82%
“…Gap junctions (GJ) allow direct communication between cells by the exchange of ions and small signaling molecules like cyclic nucleotides [9]. Gap junctional communication (GJC) occurs between endothelial [10,11], as well as between smooth muscle cells [11-14]. In small vessels, gap junctions also connect endothelial and smooth muscle cells (myoendothelial gap junctional communication, MEGJC).…”
Section: Introductionmentioning
confidence: 99%
“…In line with the work of Berra-Romani et al [29], our results show homogenous endothelial Ca 2+ signaling in response to ATP stimulation. In contrast to these results, Kameritsch et al, recently reported heterogeneous Ca 2+ responses to ATP and demonstrated a role for endothelial gap junctions in the spreading of Ca 2+ signaling in response to ATP stimulation [30]. This discrepancy could be due to differences in ATP concentrations used to stimulate endothelial cells or in the portion of the aorta used to perform the experiments.…”
Section: Discussionmentioning
confidence: 87%